Extraction and application of coloring agent of shrubby morning glory leaves (Ipomoea carnea subsp. fistulosa) as dye in batik - ZULFIYAH ZULFIYAH; ENDANG ANGGARWULAN; SITI LUSI ARUM SARI (Nusantara Bioscience, 2015)
Abstract. Zulfiyah, Anggarwulan E, Sari SLA. 2015. Extraction and application of coloring agent of shrubby morning glory leaves (Ipomoea carnea subsp. fistulosa) as dye in batik Nusantara Bioscience 7: 160-165. Natural dye is natural materials whose production is influenced by environmental factor. Natural material content affects the quality and intensity of products’ color. Shrubby morning glory (Ipomoea carnea Jacq. subsp. fistulosa (Mart. ex Choisy) D.F. Austin) has potency as a natural dye since it contains high tannin. The objective of the research is to determine the difference of tannin contents in the extract of shrubby morning glory leaves grow in field or rice field, and also the quality of batik’s color by using dyes extracted from these leaves using fixators iron sulphate (FeSO4), alum (Al2(SO4)3), and calcium oxide (CaCO3). Soil conditions observed are: soil texture, pH, nitrogen content (N), organic materials content, C-organic content. Data of the soil quality are analyzed descriptively. The result of fastness test is analyzed by Kruskal Wallis test and continued by Mann Whitney test with the significance rate of 95%. Data of tannin level are analyzed by t test-independent. The result of the study shows that the leaves of shrubby morning glory from rice-field contain high tannin, which is 1.52%. This type of soil is more fertile than field soil, with better soil texture, pH, N level, organic level, and C-organic. The fastness test shows that using extract shrubby morning glory dye which contains higher tannin is better. Batik’s dyeing using the extract of the plants growing in rice field with fixator of sulfate iron (FeSO4) has the best fastness.